2018
DOI: 10.1136/thoraxjnl-2017-210326
|View full text |Cite
|
Sign up to set email alerts
|

Airway epithelial phosphoinositide 3-kinase-δ contributes to the modulation of fungi-induced innate immune response

Abstract: BackgroundRespiratory fungal exposure is known to be associated with severe allergic lung inflammation. Airway epithelium is an essential controller of allergic inflammation. An innate immune recognition receptor, nucleotide-binding domain, leucine-rich-containing family, pyrin-domain-containing-3 (NLRP3) inflammasome, and phosphoinositide 3 kinase (PI3K)-δ in airway epithelium are involved in various inflammatory processes.ObjectivesWe investigated the role of NLRP3 inflammasome in fungi-induced allergic lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 47 publications
(60 reference statements)
0
27
0
Order By: Relevance
“…PI3K-δ has been reported to play an important role in the adaptive immune response involving T- and B-cells 7 , 32 , influencing adaptive T H 2-mediated eosinophilic inflammation. Furthermore, we have reported the crucial modulatory roles of PI3K-δ in the innate immune response at the airway epithelium partly via regulation of epithelial generation of mitochondrial ROS 11 , 12 , which are known to be essential for T H 2 cell-associated eosinophilic inflammation in airways 33 . More recently, reduction of chemokines involved in allergen-induced recruitment of T H 2 lymphocytes (namely, CCL17 and CCL22) by a potent small molecular inhibitor of PI3K-δ has been demonstrated in a phase I clinical study in patients with allergic rhinitis 34 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…PI3K-δ has been reported to play an important role in the adaptive immune response involving T- and B-cells 7 , 32 , influencing adaptive T H 2-mediated eosinophilic inflammation. Furthermore, we have reported the crucial modulatory roles of PI3K-δ in the innate immune response at the airway epithelium partly via regulation of epithelial generation of mitochondrial ROS 11 , 12 , which are known to be essential for T H 2 cell-associated eosinophilic inflammation in airways 33 . More recently, reduction of chemokines involved in allergen-induced recruitment of T H 2 lymphocytes (namely, CCL17 and CCL22) by a potent small molecular inhibitor of PI3K-δ has been demonstrated in a phase I clinical study in patients with allergic rhinitis 34 .…”
Section: Discussionmentioning
confidence: 98%
“…PI3K-δ is also likely to play key roles in generating proper effector functions of eosinophils involving the release of diverse eosinophil-derived mediators ( e.g . granular proteins, lipid mediators, cytokines/chemokines, enzymes, growth factors, and oxidative products) partly through innate receptor-mediated generation of reactive oxygen species (ROS) and pro-inflammatory cytokines 11 , 12 . Several indirect modulatory effects of PI3K-δ on eosinophilic inflammation also seem to exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SYK-CARD9 pathway also activates the NOD-, LRR-, and pyrin domain-containing 3 (NLRP3) inflammasome, which results in the proteolytic activation of the pro-inflammatory cytokines IL-1β and IL-18 by caspase 1. The role of A. fumigatus antigens in this activation cascade has been demonstrated by Jeong et al They showed that sensitized mice intratracheally challenged with A. fumigatus crude antigens displayed an increased in immunofluorescence intensities of NLRP3 and caspase-1 in lung tissue, particularly in epithelial cell layers, leading to an increase in IL1-β concentration in the lung tissue (53). Similar results were obtained by using an in vitro model utilizing primary human BECs stimulated with the same A. fumigatus antigens (53).…”
Section: Recognition Of Aspergillus Fumigatus By Bronchial Epithelialmentioning
confidence: 89%
“…The release of IL-1β in monocytes and the increased spread of pro-IL-1β is stimulated by hyphae while A. fumigatus triggers the release of NLRP3 in ammasomes [(Said-Sadier et al 2010)]. Studies showed that the expression of NLRP3 was increased in lung tissue from patients with allergic bronchopulmonary aspergillosis (ABPA)[ (Jeong et al 2018)]. For the in ammasome to induce the secretion of IL-1β the steps involved include proin ammatory stimuli triggering TLR to mediate signals, cytokines to be induced to produce proform and in ammasomes to be activated to ensure mature processing of cytokines [(Schroder and Tschopp 2010)].…”
Section: Discussionmentioning
confidence: 99%